Hubungan Pengetahuan, Sikap, dan Minat Ibu dengan Pemilihan KB Suntik di Klinik Keluarga - Susilawati, Susilawati; Jayatmi, Irma; Syarah M., Maryam (Al-Hayat: Natural Sciences, Health & Environment Journal, 2024)
Family Planning (FP) is an effort to control the birth of children, spacing, and the ideal age for giving birth to realize a quality family. This research aims to determine the relationship between the knowledge, attitudes, and interests of mothers with the choice of injectable FP at the Family Clinic in 2023. This study is an observational study with a cross-sectional design. The population in this study is all FP acceptors at the Family Clinic, totaling 67 people. The respondents in this study are FP acceptors at the Family Clinic, totaling 40 respondents. The results of the study from 40 respondents show that mothers with high knowledge are 30 people (75%), mothers with positive attitudes are 28 people (70%), and mothers with high interest are 27 people (67.5%). The Chi-Square test results for the category of maternal knowledge with the choice of injectable FP obtained a value of p = 0.000 (p = <0.05), while for the category of maternal attitude with the choice of injectable FP obtained a p-value of 0.000 < (0.05), and for the category of maternal interest with the choice of injectable FP obtained a p-value of 0.032 < (0.05). This study shows that there is a relationship between the knowledge, attitudes, and interests of mothers with the choice of injectable FP at the Family Clinic in 2023. It is advisable to always increase maternal knowledge to broaden maternal insights about FP.